2004
DOI: 10.1175/jhm-362.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soil and Vegetation Parameters in the ECMWF Land Surface Scheme

Abstract: Numerical Weather Prediction (NWP) and climate models are sensitive to evapotranspiration at the land surface. This sensitivity requires the prediction of realistic surface moisture and heat fluxes by land surface models that provide the lower boundary condition for the atmospheric models. This paper compares simulations of a stand-alone version of the European Centre for Medium-Range Weather Forecasts (ECMWF) land surface scheme, or the Viterbo and Beljaars scheme (VB95), with various soil and vegetation para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…The OzNet network is managed by the University of Melbourne. Datasets from the OzNet have been extensively used for satellite product validation (Draper et al, 2009;Liu et al, 2011;Parinussa et al, 2011) and the evaluation of land surface models (Richter et al, 2004).…”
Section: Oznetmentioning
confidence: 99%
“…The OzNet network is managed by the University of Melbourne. Datasets from the OzNet have been extensively used for satellite product validation (Draper et al, 2009;Liu et al, 2011;Parinussa et al, 2011) and the evaluation of land surface models (Richter et al, 2004).…”
Section: Oznetmentioning
confidence: 99%
“…Although NWP has improved since the implementation of LSMs, the overall performance of a forecast is still highly dependent on the initialization of soil and vegetation variables, such as soil moisture, fraction of green vegetation cover ( f c ), and leaf area index (LAI; Wetzel and Chang 1987;van den Hurk et al 1997;Crawford et al 2001;Kurkowski et al 2003;Richter et al 2004). These variables are not readily or easily observed on the scales needed to initialize NWP models, and therefore such models often rely on parameterized routines to provide a representation of the current land surface state.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the exact magnitude of this effect is uncertain. Some studies report a high sensitivity of both soil moisture and evapotranspiration to soil characteristics, such as the water-holding capacity or other soil hydraulic properties (e.g., Soet et al 2000;Seneviratne et al 2006b), while others reported mainly an effect on soil moisture (Richter et al 2004;Braun and Schä dler 2005;Kato et al 2007). The sensitivity of a LSM to its parameters also depends on the climate conditions (e.g., Pitman 1994;Bastidas et al 1999;Soet et al 2000;Liang and Guo 2003;Kahan et al 2006).…”
Section: Introductionmentioning
confidence: 99%